Identification of Circular RNA hsa_Circ_0003391 in Peripheral Blood Is Potentially Associated With Alzheimer's Disease - Liu, Li; Chen, Xi; Chen, Yu-Hua; Zhang, Ke (Frontiers in Aging Neuroscience, 2020)
Circular RNAs (circRNAs) have recently been discovered as a novel type of endogenous non-coding RNA that may regulate gene expression in mammals. In the central nervous system (CNS), circRNAs are relevant to many neurological disorders such as Alzheimer's disease (AD). In this study, we attempted to identify an aberrant circRNA, hsa_circ_0003391, which is significantly downregulated in the peripheral blood of patients with AD, and to explore the relationship between hsa_circ_0003391 and the clinical manifestation of AD. The expression of hsa_circ_0003391 had a specific decrease in the peripheral blood of patients with AD compared to those with other types of dementia. To evaluate the potential diagnostic value of the circRNA, we performed a receiver operating characteristic (ROC) curve analysis. The area under the curve (AUC) value was 0.7283 for hsa_circ_0003391, which was statistically significant. The natural form of hsa_circ_0003391 in the peripheral blood was a loop structure with good stability. We found a potential correlation between the expression of hsa_circ_0003391 and the clinical manifestations of AD. Bioinformatic analysis was carried out to predict the latent target microRNAs (miRNA) of hsa_circ_0003391. Furthermore, microRNAs targeted by hsa_circ_0003391 were successfully detected, and miR-574-5p had an expected elevation in the AD groups, suggesting that miR-574-5p might be a potential microRNA target for hsa_circ_0003391. Our results suggest that the downregulation of hsa_circ_0003391 in the peripheral blood has a potential relationship with AD. Our findings not only provide an important latent biomarker but also highlight an important perspective for the following study into AD pathogenesis. This may promote the process of novel therapeutics targeting non-coding RNA.